PENGARUH PROKRASTINASI TERHADAP HASIL BELAJAR MENGGAMBAR KONSTRUKSI KOLOM DAN BALOK BETON BERTULANG SISWA KELAS XI TGB 2 SMK NEGERI 1 PARIAMAN - Fajar Hidayat; Nurhasan Syah; Indrati Kusumaningrum (Universitas Negeri Padang, 2018)
Abstract—This research is quantitative descriptive research which aims to determine whether there is an influence of procrastination toward the learning results of Column Construction and Reinforced Concrete Beam Drawing Course of students of Class XI TGB 2 SMK Negeri 1 Pariaman in academic year 2016/2017. The population of this study is all students of Class XI TGB 2 in the academic year 2016/2017. The sample was taken by using total sampling technique. Data were collected by using questionnaires with Likert Scale consisting of 4 alternative answers. The number of statements in the research questionnaires is 24 statements. The result showed that there is a significant relationship between procrastination and the learning results with medium relationship level. From the t-test it can be concluded that there is an influence of procrastination toward the learning results of Column Construction and Reinforced Concrete Beam Drawing Course of Student of Class XI TGB 2 SMK Negeri 1 Pariaman. Keywords: Influence, procrastination, learning result